Sistem Dinamis Industri Furniture Indonesia dari Perspektif Supply Chain Management yang Berkelanjutan - Kuncoro Harto Widodo; Kharies Pramudya Dwi Arbita; Aang Abdullah (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2010)
This research aims to predict and describe the sustainability of Indonesian furniture development by considering 3 as- pects: economical revenue, social, and envieronment, as the main aspects in a sustainable supply chain. This research was started by identifying the basic model of supply chain of furniture industry. We, then, identified the potency and weaknesses from either internal or external, by using SWOT (strength, weakness, opportunity, threat) analysis. We used modeling and simulation to describe the system behaviour. The result showed the characteristics of this industry is un- certainty on consumer demand and that the industry depends on the availability of raw material from forest. There is a lack in supply in the average amount of 3.386.282 m3. The development of furniture industry needs to consider more the aspect of sustainability. Forest destruction is one of the parameters of environmental aspect, in which the decreasing rate of natural production forest and overall forest are 61,982 ha and 51,820 ha per year, respectively. Furthermore, as one of the economical aspects, the economical revenue achieved by this industry tends to constant. On the other hand, this industry can meet the consumer demand, representing the social aspect.ABSTRAKPerlu ada kajian untuk melihat dan memprediksi keberlanjutan pengembangan industri furniture Indonesia dengan melihat kepada 3 aspek, yaitu aspek ekonomi, aspek sosial dan aspek lingkungan, sebagai aspek utama dalam pengem- bangan supply chain management yang berkelanjutan. Penelitian ini diawali dengan identifikasi model dasar supply chain industri furniture. Selanjutnya, digambarkan potensi dan kelemahan yang ada, baik secara internal maupun ek- sternal, dengan menggunakan analisis SWOT (strength, weakness, opportunity, threat). Untuk melihat perilaku sistem dilakukan pemodelan dan simulasi. Hasil penelitian ini menunjukkan bahwa karakteristik industri furniture adalah ketidakpastian permintaan konsumen dan sangat tergantung pada kondisi hutan untuk menjamin ketersediaan pasokan kayu. Setiap tahun terjadi kekurangan pasokan rata-rata sebesar 3.386.282 m3 dibandingkan kebutuhannya. Pengem- bangan industri furniture masih kurang memperhatikan aspek keberlanjutan. Kerusakan hutan menjadi salah satu pa- rameter keberlanjutan aspek lingkungan dimana tingkat penurunan luas hutan produksi alam dan hutan keseluruhan berturut-turut adalah sebesar 61.982 ha dan 51.820 ha. Selain itu, dari aspek ekonomi, pendapatan (revenue) yang bisa dicapai oleh industri furniture cenderung tidak mengalami peningkatan. Di sisi lain, industri furniture Indonesia cukup baik dalam memenuhi kebutuhan konsumen, sebagai indikator aspek sosial.